+0  
 
0
85
1
avatar

1)https://vle.mathswatch.co.uk/images/questions/question2322.png

2)https://vle.mathswatch.co.uk/images/questions/question2327.png

 

The answer that I get for 1) is: r=t(r-3) 

and for the second one 2) is: t= 2-qt/7

but it says that it's wrong so pls help :)

 Jun 4, 2020
 #1
avatar+26735 
+1

First one    t = r/(r-3)    multiply both sides by (r-3)

 

tr - 3t  = r       subtract   tr from both sides

 

-3t = r - tr

-3t = r (1-t)

-3t/(1-t) = r

 Jun 4, 2020

17 Online Users

avatar